All Days 1985
DOI: 10.2118/13725-ms
|View full text |Cite
|
Sign up to set email alerts
|

Core-Annular Oil/Water Flow: The Turbulent-Lubricating-Film Model and Measurements in a 2-in. Pipe Loop

Abstract: Core-flow tests with a 3000 mPa.s fuel oil in a 2-inch test facility have revealed important information on the amplitudes and lengths of waves at the oil/water interface. The wavelengths vary considerably with water fraction and oil velocity. Moreover, the flow in the water annulus is turbulent. A previously developed theoretical model for steady core-annular flow in pipes has been extended by incorporating the effect of turbulence in the water film surrounding the oil core. Core-flow pressure gradients predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
0
13
0
3
Order By: Relevance
“…As far as liquid-liquid flows are concerned, a certain number of models dealing with core annular flow in horizontal pipes have been presented in the literature. Among them, the empirical correlations of Arney et al (1993), Oliemans et al (1987) and the mechanistic models of Brauner (1998), Ullmann and Brauner (2004), Colombo et al (2017) for oil-water flow can be cited. The basic theory underlying these models, however, assumed axis-symmetric flow of oil-water mixture and did not consider explicitly the influence of core eccentricity.…”
Section: The Work Bymentioning
confidence: 99%
See 1 more Smart Citation
“…As far as liquid-liquid flows are concerned, a certain number of models dealing with core annular flow in horizontal pipes have been presented in the literature. Among them, the empirical correlations of Arney et al (1993), Oliemans et al (1987) and the mechanistic models of Brauner (1998), Ullmann and Brauner (2004), Colombo et al (2017) for oil-water flow can be cited. The basic theory underlying these models, however, assumed axis-symmetric flow of oil-water mixture and did not consider explicitly the influence of core eccentricity.…”
Section: The Work Bymentioning
confidence: 99%
“…The vast majority of the related published work deals with viscous oilwater mixture within straight horizontal pipelines. During the past years, we can mention the works by Charles et al (1961), Ooms et al (1984), Oliemans et al (1987), Arney et al (1993), Bannwart et al (2004), Grassi et al (2008), Sotgia et al (2008), Colombo et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Totally 110 groups of CAF pressure loss data from literature (Oliemans et al, 1985;Grassi et al, 2008;Sotgia et al, 2008;Al-Wahaibi et al, 2014) and 114 groups of data in our study were used to evaluate the prediction precision of pressure loss models. The experimental data involved the oil viscosity from 12 to 3000 mPa•s, pipe diameter from 14.5 to 50.0 mm, the oil superficial velocity from 0.20 to 2.37 m/s, and the water superficial velocity from 0.03 to 1.68 m/s.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
“…Moreover, the adaptability of the model to the experiment condition of the steel pipe should also be investigated. 2014and Oliemans et al (1985).…”
Section: Discussionmentioning
confidence: 99%
“…1) Lubrication Model Ooms et al (10) and Oliemans et al (11) reported equations for estimating pressure gradient based on the hydraulic lubrication theory. Their equations require the wave length and amplitude of the oil core and thickness of the annular region, which are not easily obtainable.…”
Section: Journal Of Solid Mechanics and Materials Engineeringmentioning
confidence: 99%